DESIGN OF ACCEPTANCE INFORMATION SYSTEM OF NEW STUDENTS OF NATIONAL FLIGHT VOCATIONAL HIGH SCHOOL - DANYL MALLISZA; AMBIYAR AMBIYAR; OSKAH DAKHI; UNUNG VERAWADINA; MUHAMMAD ILHAM A SIREGAR (CV KULTURA DIGITAL MEDIA, 2021)
Acceptance of New Students of Padang National Space Flight Vocational High School conveys information about the Padang National Space Flight Vocational High School to the public through the internet. Besides, prospective students who will enroll in the Padang National Space Flight Vocational High School can make it easier for them to register online. The purpose of this research is to develop a new student registration information system at the Padang National Space Flight Vocational High School quickly and efficiently in the management and selection of prospective students. The data collection methods used in this Final Task preparation are Observation, Library Studies, and Interviews. The program using PHP and MySQL.